Active film preparation using pectin and polyphenols of watermelon peel and its applications for super-chilled storage of chilled mutton. (15th August 2023) - Guo, Zonglin; Wu, Shaozong; Lin, Jie; Zheng, Hua; Lei, Hongtao; Yu, Qunli; Jiang, Weifang
Highlights: An active film with Pectin (WMP) and polyphenols (WME) from watermelon peel for chilled mutton was developed. The addition of an appropriate amount of WME (≤1.5%) could improve the properties of WMP film. The WMP/WME film could delay the chilled mutton quality deterioration during super-chilled process. WMP/WME film performance is stable during super-chilled process. Abstract: We investigated the effect of active packaging films prepared by pectin (WMP) and polyphenols (WME) obtained from watermelon peel on the quality of chilled mutton during super-chilled storage. The addition of WME created new chemical and hydrogen bonds in film. Furthermore, an appropriate amount of WME (≤1.5%) was evenly distributed throughout the film matrix, improving barrier properties, mechanical properties, thermal stability, and light transmittance of the film. An assessment of the meat quality showed that the pH, L*, b*, thiobarbituric acid reactive substances (TBARs), total volatile basic nitrogen (TVB-N), and total bacterial count (TCA) of super-chilled + film group were significantly lower, whereas shear force and a* value were significantly higher ( P  < 0.05) than other groups. The WMP/WME film has dense microstructure and excellent mechanical properties after storage. Pectin and polyphenols obtained from watermelon peel have good potential as a novel packaging material for chilled mutton during super-chilled storage.